Organizational adaptation to working from home in a crisis situation (COVID-19): the interaction between leaders’ openness and followers’ voice - Buzás, Barnabás; Faragó, Klára (Frontiers in Psychology, 2023)
We investigated the effect of time spent at home on employee voice behavior and leadership openness during Covid 19. According to DeRue’s adaptive leadership theory which offers an interactionist perspective to explain adaptive organizational behavior during an environmental crisis, we proposed that in the WFH’s (work from home) reduced and limited communication space, leaders, who need more feedback from employees, will encourage them to express their opinions and will show more willingness to listen to them. Meanwhile, employees will ask more questions and make more suggestions to alleviate uncertainty and misunderstanding. We measured leadership openness during Covid-19 and proposed that it influences voice behavior directly and indirectly through the mediation of increasing psychological safety, intrinsic work motivation, and affective commitment. Furthermore, the increasing amount of employees’ voices will increase leadership openness. A cross-sectional study (N = 424) has been carried out with employees working from home for a different amount of their working time during the pandemic. The results showed that in the WFH situation, time spent in home office had a low but significant direct negative effect on promotive voice behavior. At the same time, leadership openness was growing with the amount of time spent at home. Leadership openness counteracted the negative effect of WFH on voice behavior: although leadership openness did not have a direct significant effect on voice behavior, it had a positive effect on psychological safety and work motivation which, in turn, influenced positively both promotive and prohibitive voice behavior. Employee’s voice, for its part, further augmented leadership openness. A mutually reinforcing process of leadership openness and employee voice took place, Leadership openness is a key factor to motivate employee voice behavior during WFH.